Therapeutic potential of broccoli-derived extracellular vesicles as nanocarriers of exogenous miRNAs. (November 2022) - del Pozo-Acebo, Lorena; López de las Hazas, María-Carmen; Tomé-Carneiro, Joao; del Saz-Lara, Andrea; Gil-Zamorano, Judit; Balaguer, Livia; Chapado, Luis A.; Busto, Rebeca; Visioli, Francesco; Dávalos, Alberto
Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression. The wide-ranging biological activities of microRNAs stimulated research on disease mechanisms and is suggesting appealing therapeutic applications. When unprotected, miRNAs suffer from rapid degradation and appropriate strategies need to be developed to improve their therapeutic potential. Since the first observation of miRNAs being naturally transported by extracellular vesicles (EVs), the latter have been proposed as specific transport means for drug delivery, conferring stability and increasing resistance against RNase degradation. However, a standard, reproducible, and cost-effective protocol for EV isolation is lacking. Here, the use of broccoli-derived EVs as a therapeutic vehicle for extracellular RNA drug delivery was assessed. EVs were isolated from broccoli, combining ultracentrifugation and size exclusion chromatography methodology. Caco-2 cells were exposed to isolated EVs loaded with exogenous miRNAs and cellular viability was tested. The miRNAs were taken up by this intestinal cell line. Our results show that broccoli EVs can be efficiently isolated, characterized, and loaded with exogenous miRNAs, leading to toxicity in caco-2 cells. Because the pharmaceutical industry is searching for novel drug delivery nanovesicles with intrinsic properties such as low immunogenicity, stability to the gastrointestinal tract, ability to overcome biological barriers, large-scale production, cost-effectiveness, etc., broccoli-isolated nanovesicles might be suitable candidates for future pharmacological applications. We propose broccoli as a natural source of EVs, which are capable of transporting exogenous miRNAs with potential therapeutic effects and suggest that appropriate toxicological and randomized controlled trials as well as patent applications are warranted. Graphical Abstract: ga1